Diabetes-related defects in sarcoplasmic Ca2+ release are prevented by inactivation of Gα11 and Gαq in murine cardiomyocytes - Hoyer, Dieter Paul; Grönke, Sabine; Frank, Konrad F.; Addicks, Klaus; Wettschureck, Nina; Offermanns, Stefan; Erdmann, Erland; Reuter, Hannes (Molecular and cellular biochemistry, 2010)
Neurohumoral stimulation of Gq-coupled receptors has been proposed as a central mechanism in the pathogenesis of diabetic heart disease. The resulting contractile dysfunction is closely related to abnormal intracellular Ca2+ handling with functional defects of the sarcoplasmic reticulum (SR). The present study was therefore designed to determine the role of Gq-protein signaling via Gα11 and Gαq in diabetes for the induction of functional and structural changes in the Ca2+ release complex of the SR. An experimental type 1-diabetes was induced in wild type, Gα11 knockout, and Gα11/q-knockout mice by injection of streptozotocin. Cardiac morphology and function was assessed in vivo by echocardiography. SR Ca2+ leak was tested in vitro based on a 45Ca2+ assay and protein densities as well as gene expression of ryanodine receptor (RyR2), FKBP12.6, sorcin, and annexin A7 were analyzed by immunoblot and RT-PCR. In wild type animals 8 weeks of diabetes resulted in cardiac hypertrophy and SR Ca2+ leak was increased. In addition, diabetic wild type animals showed reduced protein levels of FKBP12.6 and annexin A7. In Gα11- and Gα11/q-knockout animals, however, SR Ca2+ release and cardiac phenotype remained unchanged upon induction of diabetes. Densities of the proteins that we presently analyzed were also unaltered in Gα11-knockout mice. Gα11/q-knockout animals even showed increased expression of sorcin and annexin A7. Thus, based on the present study we suggest a signaling pathway via the Gq-proteins, Gα11 and Gαq, that could link increased neurohumoral stimulation in diabetes with defective RyR2 channel function by regulating protein expression of FKBP12.6, annexin A7, and sorcin.